Современный русский литературный язык: учебное пособие - Михалева Е. В. Елена Владимировна; Мишанкина Н. А. Наталья Александровна; Курикова Н. В. Наталья Владимировна; Вавилова Е. Н. Елена Николаевна (Томск, Изд-во ТПУ, 2010)
Заглавие с титульного экрана